THE NATURE OF CHILDREN'S READING IN CLASSICAL LITERATURE (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article is dedicated to the giants of children's reading associated with classical literature. The article uses examples of classical Uzbek literature.